Consciousness of Racial Equality as Reflected in Michael Jackson’s “Black or White” - Kirana, Devi (LANTERN (Journal on English Language, Culture and Literature), 2014)
In a revealing expression and feeling, the author uses an analysis with the meaning of the lyrics of the song created. This final paper contains about racial equality described in the lyrics of Michael Jackson's